Effectiveness of opiate substitution treatment in reducing HIV risk behaviors among African, Caribbean and black people: a systematic review protocol. Issue 3 (March 2020) - Nguemo Djiometio, Joseph B.; Mohamud, Hodan; Njoroge, Irene; Nelson, LaRon E.; Kahan, Meldon
ABSTRACT: Objective: This systematic review aims to identify, appraise and synthesize the best available evidence on the effectiveness of methadone maintenance treatment or buprenorphine therapy in reducing sex- and drug-related HIV risk among African, Caribbean and black people. Introduction: Substance use plays an important role in HIV transmission and acquisition among African, Caribbean and black people by increasing risky sexual behavior and the risk of HIV acquisition. Pharmacological interventions targeting drug use, injection-related risk behaviors and HIV risk behaviors have been found to be effective measures in minimizing HIV transmission attributable to opioid addiction. Inclusion criteria: This review will consider studies that have evaluated the impact of methadone maintenance treatment or buprenorphine therapy on sex- and drug-related HIV risks. All interventions conducted in any clinical setting will be included. Methods: Multiple sources of published and gray literature will be searched, including Embase, MEDLINE, PsycINFO, Cochrane Central Register of Controlled Trials, OpenGrey, Grey Matters, New York Academy of Medicine's Grey Literature Report, ClinicalTrials.gov and WHO International Clinical Trials Registry Platform. All titles and abstracts identified will be reviewed independently by two reviewers and potentially relevant studies will be retrieved in full. Papers selected for retrieval will be assessed by two independent reviewers for methodological validity. Data will be extracted from papers and will include details about the interventions, populations, study methods and outcomes. Systematic review registration: PROSPERO CRD42019126954.